Charity of the Orthodox Brotherhoods of Left Bank Ukraine (1864 – 1917) - Сергієнко, В. (Київський національний університет імені Тараса Шевченка, 2012)
The article is devoted to the investigation of charity of the orthodox brotherhoods of Left bank Ukraine in 1864 – 1917 y. The attainments of the brotherhood organizations were defined by the main areas of charitable activity. The peculiarities of church public charity of the brotherhoods during World War I were described.

Стаття присвячена дослідженню благодійності православних церковних братств Лівобережної України в 1864 – 1917 рр. Схарактеризовано здобутки братських організацій за основними напрямками благодійництва. Визначено особливості церковно-громадської благодійності братств під час Першої світової війни.
Благодійність православних церковних братств Лівобережної України (1864 – 1917)
Keywords: особливий шлях (Sonderweg); німецька історіографія; порівняльно-історичний метод; Sonderweg; German historiography; comparative-historical method